TANTANGAN EKSISTENSI PEMIMPIN DALAM MENGELOLA SDM DI ERA DIGITAL - Novia Purnamasari; Martin Agusta; Isniar Budiarti; Dedi Sulistiyo; Siti Kurnia Rahayu (UM. Bengkulu, 2026)
Digital transformation in healthcare services demands leadership that is not only adaptive to technological change but also capable of integrating knowledge, ethical values, and humanistic dimensions in human resource management. This study aims to analyze the existence of digital leadership at MAS Clinic from the perspective of the philosophy of science, particularly through the ontological, epistemological, and axiological dimensions. The research employs a qualitative approach with a reflective case study design within an interpretive paradigm that views social reality as a construction of meaning shaped through interpersonal interactions. Data were collected through in-depth interviews with leaders and staff, participatory observation of work processes, and digital documentation capturing managerial dynamics and clinical service practices. The findings reveal that leadership at MAS Clinic, ontologically, perceives staff as meaningful subjects embedded within a collectivist socio-cultural context, thereby manifesting leadership presence in an authentic and participatory manner. Epistemologically, leaders facilitate the creation of collective knowledge through digital-based mentoring and the SECI process by integrating tacit knowledge, explicit knowledge, and real-time digital data. Axiologically, digital leadership is oriented toward strengthening ethical values, humanism, and patient safety as primary priorities, while fostering an innovation culture grounded in moral values. These findings affirm that effective digital leadership in local healthcare service contexts is inherently humanistic and contextual rather than purely technocratic. Theoretically, this study contributes to the discourse on digital leadership grounded in the philosophy of science, while practically offering strategic references for clinic managers in implementing ethical and human-centered digital transformation. Keywords: Digital Era, Leadership Existence, Healthcare Clinic, Human Resource Management, Leadership Challenges.